REKONSTRUKSI SEKEHE TERUNA DI KUTAUNTUK PERLINDUNGAN BUDAYA BALI - I Wayan Wahyu Wira Udytama; Putu Sekarwangi Saraswati (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2018)
The Ajeg Bali Movement leads to an increase in the strength of the Balinese youth so as not to fall in the conquest of global culture. The role of Balinese youth in the Kuta area in maintaining Balinese culture through youth organizations such as sekehe teruna is very important for the development of Balinese culture does not shift the culture of Bali, especially the youth culture in organizational life sekehe teruna, so that the reconstruction of the organization sekehe teruna needed to maintain Balinese culture.The role of Balinese youth in the Kuta area in maintaining Balinese culture through youth organizations such as sekehe teruna is very important for the development of Balinese culture does not shift the culture of Bali, especially the youth culture in organizational life sekehe teruna, so that the reconstruction of the organization sekehe teruna needed to maintain Balinese culture. Develop mechanisms and assess the findings, analyze the strengths, weaknesses, opportunities and challenges in the effort to control the conversion of rice fields and the strengthening of Balinese customary law. Provide input and scientific study in determining the policy in accordance with the expectations, and the state of rural communities in Bali both in the long term and in the short term. Assessing the extent to which the traditional villages of Kuta and sekehe teruna understand and explore the benefits of Balinese cultural reconstruction. Data were collected through in-depth interview, observation, focus group discussion, and RRA data were analyzed descriptively-qualitative. Score data (Likert Scale) is used to determine the strategy of determining the duration of reconstruction for the young people in protecting Balinese culture. Followed by SWOT analysis on system components of mindset, social system, and physical system. SWOT analysis result, will be made strategy of preserving Balinese culture and exploiting reconstruction sekehe teruna in protecting Bali culture well in accordance with the circumstances of indigenous villages of Kuta.